All‐Inorganic Lead‐Free Perovskite(‐Like) Single Crystals: Synthesis, Properties, and Applications. Issue 5 (23rd February 2021) - Zhao, Shuangyi; Cai, Wensi; Wang, Huaxin; Zang, Zhigang; Chen, Jiangzhao
Abstract: Due to their nontoxicity, stability, and unique optoelectronic properties, all‐inorganic lead‐free halide semiconductors with perovskite and perovskite‐like structures have successfully emerged as promising optoelectronic materials for various applications, such as solar cells, light‐emitting diodes (LEDs), photodetectors, and X‐ray detectors. To further explore their practical potentials, researchers have paid more attention in all‐inorganic lead‐free perovskite (‐like) (ILFP) single crystals. For these single crystals, the advantages of large sizes, uniform surface morphology, and few defects can facilitate their excellent performances and practical applications. Besides, compared with the low dimensional and polycrystalline ILFP materials, the ILFP single crystals feature enhanced performances, including a longer carrier diffusion length and a larger light absorption coefficient, which attract a great deal of attention. Therefore, focus is on the researching progress of ILFP single crystals and the development of their preparation methods, as well as the novel properties of ILFP single crystals. In addition, the reported applications of ILFP single crystals are proposed to highlight their practical importance. With the perspective of the evolution and challenges, the current limitations of the materials and devices are discussed, followed by an inspirational outlook on their future development directions. Abstract : The recent developments of all‐inorganic lead‐free perovskite (‐like) single crystals are systemically summarized, including the synthesizing methods, properties, and excellent stabilities. In addition, their wide applications, such as photodetectors, scintillators, X‐ray detectors, and white light‐emitting diodes, are demonstrated, followed by the discussion of current challenges and perspectives.